Effect of Silica Fume & Steel Slag on Nano-silica based High-Performance Concrete. Issue 1 (November 2020) - Kansal, C M; Singla, S; Garg, R
Abstract: This study presents strength behaviour of concrete based composites including three different ternary binders namely Nano-Silica (NS), Silica Fume (SF) & Steel Slag (SS). NS as fragmental substitution of cement, SF as the fragmental substitution for the fine aggregates and SS as fragmental substitution of coarse aggregates has been used. The study has been conducted at an optimized content of NS (2%) and by varying the content of SF (10-15%) and SS (10-30%). Cement concrete having M60 grade strength at fixed W/C (0.35) has been explored for the strength behaviour. The studies have revealed that the optimized content of NS, SF and SS can be used as a partial substitute of cement, fine aggregates and coarse aggregates respectively to obtain increased strength. Thus, NS, SF and SS can be used to obtain high performance and eco-friendly concrete structures.